Level of physical activity of physical education students in Poland and Ireland - Michał Górski; Monika Piątkowska; Anna Pastuszak; Bartłomiej Michalak (Kazimierz Wielki University, 2017)
Introduction: In order to prevent adverse changes in lifestyle, leading to the deterioration of health, it is important to continuously monitor the level of physical activity, particularly among young people Aim of study: Evaluation and  comparative analysis of physical activity level of Polish and Irish physical education students. Material and methods: The analysis was based on 159 IPAQ questionnaires (long version of the questionnaire on the last 7 days), filled by physical education students at the Józef Pilsudski Academy of Physical Education in Warsaw, (AWF) in Poland and the University of Limerick in Ireland (UL).Results: level of physical activity of students from Poland was significantly higher (p < 0.05) than students in Ireland, respectively 11477 ± 6331 MET and 7205 ± 4787 MET. The largest differences were recorded in the work domain of the questionnaire. This part of questionnaire is about energy expenditure on activities performed at work and during classes. Male and female students from Poland had significantly higher (p < 0.05) energy expenditure on vigorous-intensity activity. Female Polish students have also higher energy expenditure on moderate-intensity activity and on walking. Irish people spend significantly more time on sitting during weekdays and weekends compared to students from Poland (p <0.05).Conclusion: The size of the differences in the first domain of the questionnaire were caused by slightly different design of the first question in Polish and English versions of the questionnaire. In order to avoid different interpretations of the questions, we recommend to apply the method of the direct interview conducted by specifically trained interviewers.